What Can We Glean from the Past Seven Decades of Voluntary Carbon Emissions Disclosure Research? - Mohamad, Maslinawati; Abd Rahman, Noor Raida; Nahar, Hairul Suhaimi; Alfi, Coky Fauzi (International Journal of Energy Economics and Policy, 2023)
This paper provides a comprehensive analysis of global research on carbon emission disclosure, highlighting the challenges associated with climate change and its impact on businesses. To achieve this, the study analysed a dataset comprising 745 publications that were published between 1953 and 2022, obtained from the Scopus database, using bibliometrics, content analysis, and network approach methods. The results, analysed using VOSViewer, MS Excel, and Harzing's Publish or Perish software, revealed that voluntary carbon emission disclosure (VCED) is a crucial area of study. The analysis identified various themes and highlighted limitations in the literature's growth while offering suggestions for further research. The study employed a combination of bibliometric, content, and network analyses to investigate carbon emission disclosure.